2022
DOI: 10.1039/d1ta09627c
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of ruthenium nanoparticles over NiV-LDH surface for enhanced electrochemical water splitting: an oxygen vacancy approach

Abstract: In a search of alternates for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), out of various transition metal based electrocatalysts, layer double hydroxide (LDHs) based materials are attracted...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 65 publications
0
52
0
Order By: Relevance
“…In addition, to many systems, OER in the presence of Pd or Pt foils and [FeO 4 ] 2– were investigated under alkaline conditions (pH ≈ 13). , Comparing Pd, Ti, Ni, Pt, and Cu in the absence of the Fe salt points to a clear difference in the OERs. The difference in OERs for these metals is predictable since the conductivity and other properties of these metals are different (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, to many systems, OER in the presence of Pd or Pt foils and [FeO 4 ] 2– were investigated under alkaline conditions (pH ≈ 13). , Comparing Pd, Ti, Ni, Pt, and Cu in the absence of the Fe salt points to a clear difference in the OERs. The difference in OERs for these metals is predictable since the conductivity and other properties of these metals are different (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that the Ni coordination compound species form aggregations of molecular species before the decomposition and then decompose to Ni (hydr)­oxide. Different methods have been reported for synthesizing OER catalysts, and the decomposition of metal coordination compounds is also a promising method for this purpose.…”
Section: Results and Discussionmentioning
confidence: 99%
“…26,27 Notably, the cost of Ru 0 with Pt-like HER activity is only 4% that of Pt and it is considered to be one of the most promising precious metal catalysts. [28][29][30] However, the adsorption capacity of Ru 0 for H* is very strong, which is not conducive for the Tafel step of the HER. 31 Therefore, it is crucial to use interfacial engineering strategies to readjust the electron density around Ru and optimize the adsorption of reaction intermediates.…”
Section: Introductionmentioning
confidence: 99%